2019
DOI: 10.1021/acsami.9b17507
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving Linear-Velocity by Multiphoton Upconversion

Abstract: Up to now, the rising edge of the upconversion process does not receive due attention. Herein, a demonstration utilizing the feature of the rising edge to practically detect the linear-velocity of an object is presented. Typically, upconversion processes with different numbers of participant photons would exhibit diversity in the rising edge. On this account, when the emitter is moving, the emission intensity ratio of different multiphoton processes will vary with changing linear-velocity, which enables accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The emission color of the stamped patterns achieved with NaErF 4 : 10Yb@NaYF 4 @NaYbF 4 : 20Ca/1Tm@NaYF 4 NCs (124 nm, Figure S15a) and NaErF 4 : 10Yb@NaYF 4 @NaYbF 4 : 20Li/20Ca/1Tm@NaYF 4 core/triple-shell NCs (57 nm, Figure S15b), which were invisible under daylight, changed evidently with the increase of the excitation power density. It has been reported that Er 3+ and Tm 3+ ions in the Yb/ Tm:NaGdF 4 @NaYF 4 @Yb/Er:NaGdF 4 core/dual-shell NCs showed temporal color separation owing to their different rising edge in the decay life-time curves [39]. As shown in Figure S16, the rising edge among the transitions of 1 G 4 → 3 H 6 , 1 D 2 → 3 H 6 , Er 3+ : 4 S 3/2 → 4 I 15/2, and 4 F 9/2 → 4 I 15/2 as well as their corresponding life-time are distinctly different, hence, temporal multicolor is anticipates to be achieved with rotating the as-prepared patterns.…”
Section: Characterizationsmentioning
confidence: 99%
“…The emission color of the stamped patterns achieved with NaErF 4 : 10Yb@NaYF 4 @NaYbF 4 : 20Ca/1Tm@NaYF 4 NCs (124 nm, Figure S15a) and NaErF 4 : 10Yb@NaYF 4 @NaYbF 4 : 20Li/20Ca/1Tm@NaYF 4 core/triple-shell NCs (57 nm, Figure S15b), which were invisible under daylight, changed evidently with the increase of the excitation power density. It has been reported that Er 3+ and Tm 3+ ions in the Yb/ Tm:NaGdF 4 @NaYF 4 @Yb/Er:NaGdF 4 core/dual-shell NCs showed temporal color separation owing to their different rising edge in the decay life-time curves [39]. As shown in Figure S16, the rising edge among the transitions of 1 G 4 → 3 H 6 , 1 D 2 → 3 H 6 , Er 3+ : 4 S 3/2 → 4 I 15/2, and 4 F 9/2 → 4 I 15/2 as well as their corresponding life-time are distinctly different, hence, temporal multicolor is anticipates to be achieved with rotating the as-prepared patterns.…”
Section: Characterizationsmentioning
confidence: 99%
“…This type of calibration applies to the majority of velocimetry methods based on the use of a luminescent probe, whose luminescent profile can be recorded and calibrated with varying the flow velocity. [3][4][5] Lanthanide-doped upconverting nanoparticles (UCNPs) have been previously adopted for velocity measurements, and the ratio between specific emissions provided the velocity after calibration. [4][5] The limitations of these methods reside in the propagation of the errors to the measured velocities arising from the external parameters used for calibration and from the deconvolution of the luminescence profile, and the necessity to repeat the calibration after any modifications of the experimental setup.…”
Section: Doi: 101002/adma202002266mentioning
confidence: 99%
“…Also, it requires calibration of the CIE coordinates with time, resulting in a similar approach to the ones already reported in the literature. [3][4][5] A more flexible way to obtain the particle velocities, without any need for calibration, is achieved by applying blue and green bandpass filters (BP450 and BP540, respectively) to capture the flow as images. In contrast to the color-coordinate method, the influence of the sensitivity of different detectors does not constitute a source of error when the multiple emissions are recorded separately.…”
Section: Evaluation Of Particle Dynamics At the Nano-and Microscale Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the decades, lanthanide (Ln 3+ )‐doped materials have been widely applied in broad areas owing to the excellent optical, electrical, and magnetic properties, such as color display, solar cells, detection technology, and temperature sensors 1‐9 . Recently, Ln 3+ ‐doped materials have attracted significant attention in the area of biotechnology as fluorescent and thermal probes.…”
Section: Introductionmentioning
confidence: 99%